KETERCAPAIAN PERWUJUDAN LINGKUNGAN PERMUKIMAN LAYAK HUNI DALAM RANGKA PROGRAM PENATAAN LINGKUNGAN PERMUKIMAN BERBASIS KOMUNITAS (PLPBK) DI KABUPATEN KARANGANYAR - Diana Putri Wijayanti; Murtanti Jani Rahayu; Rizon Pamardhi Utomo (ARSITEKTURA, 2015)
Poverty and slums are two things that can not be separated and a problem that often occurs in a region. Just as Karanganyar which has a fairly high level of poverty, it also illustrates the low quality of life. therefore implemented PLPBK program as a form of government intervention in housing issues. However, in practice there are problems that the program is considered less able to resolve the housing problem. This study was conducted to determine how the program realizes a good settlement in the framework of the program PLPBK in Karanganyar. This study not only look at the extent to which an increase in physical conditions that occur after the implementation of the program, but also how the level of the physical condition of the environmental suitability criteria habitable settlements are seen on the circumstances of each physical element neighborhoods include commercial facilities, educational facilities, health facilities, public service facilities, open space facilities, roads, drainage, sewage, garbage and water. The conclusion by looking at the physical condition of the environment in the study area is known that the physical condition of the environment has increased high at 74.3%, while for the level of suitability of the physical condition of settlements with settlement criteria livable rated high at 87.2%. So that the known increase in the level of suitability and physical condition of neighborhoods, achievement embodiment livable neighborhoods in order PLPBK program in Karanganyar assessed achieved Keyword : livable, settlements, PLPBK